2012
DOI: 10.1073/pnas.1212597109
|View full text |Cite
|
Sign up to set email alerts
|

αvβ3-integrin is a major sensor and activator of innate immunity to herpes simplex virus-1

Abstract: Pathogens are sensed by Toll-like receptors (TLRs) and a growing number of non-TLR receptors. Integrins constitute a family of signaling receptors exploited by viruses and bacteria to access cells. By gain- and loss-of-function approaches we found that αvβ3-integrin is a sensor of and plays a crucial role in the innate defense against herpes simplex virus (HSV). αvβ3-integrin signaled through two pathways. One concurred with TLR2, affected activation/induction of interferons type 1 (IFNs-1), NF-κB (nuclear fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(112 citation statements)
references
References 51 publications
5
107
0
Order By: Relevance
“…This is supported by evidence that integrins can serve as specific receptors for EBV and HSV gH/gL and may provide the viral fusion trigger or promote viral endocytosis (64,(96)(97)(98)(99). Competition studies have revealed that cell surface expression of the PC, but not the gH/gL complex, the UL128/ UL130/UL131a complex, or gB, on the surfaces of epithelial cells can prevent CMV infection, implying that the PC may be involved in receptor binding by the virus (34) (Fig.…”
Section: Gh/gl Complexes Critical Determinants Of Tropismmentioning
confidence: 68%
“…This is supported by evidence that integrins can serve as specific receptors for EBV and HSV gH/gL and may provide the viral fusion trigger or promote viral endocytosis (64,(96)(97)(98)(99). Competition studies have revealed that cell surface expression of the PC, but not the gH/gL complex, the UL128/ UL130/UL131a complex, or gB, on the surfaces of epithelial cells can prevent CMV infection, implying that the PC may be involved in receptor binding by the virus (34) (Fig.…”
Section: Gh/gl Complexes Critical Determinants Of Tropismmentioning
confidence: 68%
“…Importantly, these studies were performed with virus and human cells, rather than recombinant and/or tagged viral proteins, as the structure and function of individual components may be impacted by viruscell interactions and other envelope glycoproteins. Indeed, no interaction between gH and ␣v␤3 was detected by proximity ligation assay in response to ⌬gD or ⌬gB virus (expressing gH), although soluble gH-gL can bind to immobilized integrin ␣v␤3 (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, other work also links the virusinduced Akt/integrin/Ca 2ϩ cascade to innate immune responses. For example, using 293T cells, Campadelli-Fiume and colleagues have shown that integrin ␣v␤3 relocates HSV-1 to cholesterol-rich membrane microdomains where the virus activates innate responses through Toll-like receptor 2 (TLR2)-dependent and TLR2-independent pathways (16). Moreover, HSV virus-like particles induced the expression of interferon-stimulated genes, including CXCL10 in dendritic cells, but the response was dependent on Akt activation, as drugs that blocked Akt phosphorylation prevented the CXCL10 response (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether ␣v␤3 integrin acts in concert with plasma membrane TLRs other than TLR2, we made use of a 293T-derivative cell line in which ␤3 integrin was stably silenced by means of a lentivirus encoding a short hairpin RNA (shRNA; herein called 293Tsh␤3 cells). Depletion of ␤3 integrin was ascertained through a 70% reduction in both ␤3 mRNA and ␤3 protein compared to those in cells transduced with a control shRNA (14,15). We measured the NF-B activation in 293T and 293Tsh␤3 cells transfected with the appropriate TLRs and exposed to HSV or bacterial PAMPs.…”
mentioning
confidence: 99%